2016
DOI: 10.26858/eltww.v3i2.2261
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s questioning and students’ critical thinking in EFL classroom interaction

Abstract: The present study intended to examine the levels of questions based on Bloom’s Taxonomy used in EFL classroom interaction, to investigate the teacher’s questioning techniques and to analyze the roles of teacher’s questioning on students’ critical thinking. This study applied qualitative descriptive method. Classroom observation, field notes and interview were employed. The study engaged an English teacher at SMA Negeri 1 Tolitoli. The result showed that the teacher asked four out of six levels of questions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…Barjesteh and Moghadam (2014) have also explained that teachers ask questions for two reasons: (1) to stimulate students’ active participation, and (2) to control the progress of teacher–student interaction so as to adjust instructional pace according to students’ understanding. Moreover, Yuliawati et al. (2016) suggested that the questioning strategy helps students develop their interest in the lesson content by promoting students’ rational thoughts, allowing teachers to eliminate their confusing thoughts, highlighting important ideas and concepts, evaluating their understanding, and encouraging their participation in the lesson.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Barjesteh and Moghadam (2014) have also explained that teachers ask questions for two reasons: (1) to stimulate students’ active participation, and (2) to control the progress of teacher–student interaction so as to adjust instructional pace according to students’ understanding. Moreover, Yuliawati et al. (2016) suggested that the questioning strategy helps students develop their interest in the lesson content by promoting students’ rational thoughts, allowing teachers to eliminate their confusing thoughts, highlighting important ideas and concepts, evaluating their understanding, and encouraging their participation in the lesson.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reading is also the most fundamental skill for nearly all academic subjects, students’ educational success, and their later careers ( Okkinga et al., 2018 ). Therefore, in teaching reading comprehension skills, teachers should use the most effective teaching strategies to stimulate students’ critical thinking ( Yuliawati et al., 2016 ). Among those strategies, the questioning strategy can affect students’ active learning participation ( Nuryani et al., 2018 ), so most teachers currently use the questioning strategy to elicit students’ responses, check their understanding, and control their behavior ( Yuliawati et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations